Trichoderma- from lab bench to field application: Looking back over 50 years - Dutta, Pranab; Deb, Lipa; Pandey, Abhay K. (Frontiers in Agronomy, 2022)
Biological control of plant pathogens has become increasingly possible with the use of fungi, which have a high reproductive rate (both sexually and asexually), a short generation time, and are very specific to their target. Trichoderma species are found in diverse habitats and experience various interactions with other organisms. They are used as bio-fungicides owing to their plant-protecting abilities and they produce a large amount of secondary metabolites accompanied by enrichment in secondary metabolism-associated genes. This article aims to review and discuss the secondary metabolites produced by Trichoderma species, including their physiology, mode of action, mass production, and industrial and field applications for the control of plant diseases. We discuss the evolutionary history, taxonomical gradient, classification, and ecology of Trichoderma species, as well as indirect and direct mechanisms used as plant protectors with gene improvement strategies. Aside from the bioactivity of secondary metabolites derived from Trichoderma species, compatibility with fungicides, mass formulation techniques, and industrial applications of Trichoderma species, the review focuse on its advent and progress as a global research pioneer.